Identity Construction and Cultural Negotiation in Second Generation Urban Migrants - Besse Nurfaiqah (Generasi Sains Indonesia, 2025)
This article examines the identity construction and cultural negotiation processes experienced by second-generation migrants in urban areas. Using a qualitative approach through case studies and in-depth interviews, this research highlights how second-generation migrants construct transnational identities that are fluid, hybrid, and contextual. The results show that they face challenges in the form of discrimination, stereotypes, and social pressures that often lead to identity crises, but also open up space for cultural resistance and creativity. Digital media plays a crucial role as a means of self-expression and the formation of transnational imagined communities, strengthening transnational connectedness and identity flexibility. These findings emphasize that second-generation migrant identities are not simply inherited from family but are dynamically shaped through social interactions, daily experiences, and the flow of globalization.